Sumber Primer Pendidikan Islam Sebagai Upaya Membentuk Akhlak Anak Generasi Penerus Bangsa - Bunayar - Bunayar; M. Choirul Muzaini; Anis - Mahmudah; Sutrisno - Sutrisno (DIMAR: Jurnal Pendidikan Islam, 2022)
The highest authority in Islam is the Qu’an. It is the beginning of faith, worship, morality and principles. One thing that should be taught to children is that the entire Qur'an is a guide for human life. The verses of the Qur'an and related sources can be a gateway for children to other Islamic educational tools, especially for passion and deepening of religious knowledge to develop healthy morals in accordance with Islamic law. Learning is seen as a lifelong learning process. Al-Qur'an teaching plays an important role in the formation of children's morals by providing guidance, lifelong learning and guidance on the formation of morals from an early age. Al-Qur'an and education play a role here, namely forming morals that are in accordance with the nation's civilization and developing the ability to educate people's lives. Islamic education is also a formal institution that organizes education based on the Qur'an with the aim of forming children's morals.